VARIASI RESPONS KEPATUHAN TERHADAP INTERVENSI EDUKASI TERAPI MALARIA VIVAX BERDASARKAN KARAKTERISTIK PASIEN DI DAERAH ENDEMIK TINGGI MALARIA, PAPUA - Sahiddin, Muhamad; Nasrah; Suprayitno, Guruh; Asrianto (LPPM STIKES BINA GENERASI POLEWALI MANDAR, 2026)
Adherence to a 14-day primaquine regimen is essential for the radical cure of Plasmodium vivax malaria, yet adherence levels may vary across patient characteristics. This study examined variations in adherence to primaquine therapy based on sociodemographic, clinical, and environmental factors among P. vivax malaria patients in Jayapura City, Papua. A quantitative study was conducted among 278 patients attending six primary health centers, with adherence to primaquine for 14 days assessed using a per-protocol approach and pill count method. Patients were classified as having received specific education or not received specific education regarding primaquine therapy. Subgroup analyses were performed using the Chi-square test, and results were presented as risk ratios (RR) with 95% confidence intervals (CI). Adherence was higher among patients who received specific education (85.0%) compared with those who did not (61.8%; RR = 1.37; 95% CI: 1.19–1.58; p < 0.001). Higher adherence was observed among patients aged 15–29 years (RR = 1.32; 95% CI: 1.05–1.68; p = 0.017) and ≥30 years (RR = 1.75; 95% CI: 1.29–2.30; p = 0.002), patients with a history of malaria relapse (RR = 1.64; 95% CI: 1.30–2.08; p < 0.001), those living near swamp or lake areas (RR = 1.68; 95% CI: 1.18–2.38; p = 0.003), and patients who experienced drug side effects (RR = 2.33; 95% CI: 1.53–3.56; p < 0.001). These findings indicate that adherence to primaquine therapy varies according to patient characteristics, suggesting the need for targeted educational strategies tailored to specific patient profiles to improve adherence to radical cure treatment for P. vivax malaria.